Pengaruh Pembiayaan Murabahah Terhadap Laba Melalui Variabel Intervening Pembiayaan Bermasalah Bank Umum Syariah di Indonesia Periode 2009-2013 - Afif, Zaim Nur; Mawardi, Imron (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to investigate the effect of murabaha financing to profit through non performing financing as an intervening variable of islamic banks in Indonesia. This study uses quantitive approach with path analysis and three kinds of variables, they are murabaha financing as exogenous variable, non performing financing as intervening endogenous variable and profit as endogenous variable. The banks are used in this study is the Bank Muamalat Indonesia, Bank Syariah Mandiri, Bank Mega Syariah, Bank BRI Syariah, and Bank Syariah Bukopin. This study uses secondary data. Data collection is conducted by collecting semester financial statements for 2009-2013 period.The results obtained that, murabaha financing has positive effects to non performing financing. It also happens to the effect of murabaha financing to profit. Meanwhile, non performing financing does not have effect to profit.